Examining the utility of cystatin C as a confirmatory test of chronic kidney disease across the age range in middle-aged and older community-dwelling adults. - Little, Mark; Kenny, Rose (My University, 2018)
Background: Cystatin C has been proposed as a confirmatory test of chronic kidney disease (CKD). This is most applicable to older individuals with CKD, the majority of whom have a creatinine-based estimated glomerular filtration rate (eGFR) of 45–59 mL/min/1.73 m2 (CKD stage 3a). We sought to examine the utility of cystatin C as a confirmatory test of CKD across the age range in the general population of older adults. Methods: Cross-sectional analysis of 5386 participants from The Irish Longitudinal Study on Ageing, a cluster-sampled national cohort of community-dwelling adults aged ≥50 years. Cystatin C and creatinine were measured simultaneously using standardised assays. Using generalised additive models, we modelled the distributions of creatinine and cystatin C per year of age from four distributional parameters: location, dispersion, skewness, kurtosis. Among participants with CKD stage 3a, we estimated the predicted probability of cystatin C eGFR <60 mL/min/1.73 m2 (‘confirmed CKD’) as a function of age. Results: Median age was 62 years, 53% were female and median cystatin C eGFR was 80 mL/min/1.73 m2. We observed progressive variability in cystatin C with increasing age. Compared with creatinine, cystatin C levels rose sharply beyond the age of 65. Among participants with CKD stage 3a (n=463), the predicted probability of ‘confirmed CKD’ increased steadily with age, from 15% at age 50 to 80% at age 80. Conclusions: The clinical utility of cystatin C may be maximised in middle-aged individuals, in whom the distribution of cystatin C is less variable than older adults, and the pretest probability of confirming CKD is lower.
PUBLISHED
Keywords: Older adults; Middle age; Cystatin C; Chronic kidney disease; Ageing